2011
DOI: 10.1097/ccm.0b013e3181fa7ce4
|View full text |Cite|
|
Sign up to set email alerts
|

Take Heart America: A comprehensive, community-wide, systems-based approach to the treatment of cardiac arrest*

Abstract: The Take Heart America program doubled cardiac arrest survival when compared with historical controls. Study of the feasibility of generalizing this approach to larger cities, states, and regions is underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 31 publications
1
65
0
1
Order By: Relevance
“…154,156,158,163,165,[167][168][169][170][172][173][174] Three studies examined neurologic intact survival at 30 days. 154,170,173 The other 9 studies reported survival to hospital discharge with good neurologic outcome.…”
Section: October 20 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…154,156,158,163,165,[167][168][169][170][172][173][174] Three studies examined neurologic intact survival at 30 days. 154,170,173 The other 9 studies reported survival to hospital discharge with good neurologic outcome.…”
Section: October 20 2015mentioning
confidence: 99%
“…[155][156][157][158][159][160][161][162][163][164] Six observational studies compared OHCA patient survival outcomes before and after the implementation of a regionalized system of postresuscitation care. [165][166][167][168][169][170] Six observational studies compared patient…”
Section: Consensus On Sciencementioning
confidence: 99%
“…11 This update on OHCA resuscitation systems of care describes recent advances, evidence Since 2010, many municipalities and regions have continued or begun to implement cardiac resuscitation systems modeled on prior experience implementing and maintaining similar interconnected systems for patients with traumatic injury, STEMI, and acute stroke. To assist in the evolution of regional resuscitation systems of care, several national organized efforts have emerged, including Mission: Lifeline, 16,17 Take Heart America, 18 and the HeartRescue Project. 19 Each of these initiatives is intended to facilitate implementation of evidencebased treatments across the continuum of care delivery and to establish an interconnected community, EMS, and hospital response to improve cardiac arrest outcomes.…”
mentioning
confidence: 99%
“…These first responders perform continuous CPR and apply AED until the arrival of an ALS team. A 2-tier system outside the EMS can shorten call-to-defibrillation time; and it may improve outcome if the call-to defibrillation time is reduced to a few minutes, especially in areas where an ALS team is not rapidly available [3,15,[45][46][47][48][49][50]. Some studies did not report improved outcomes because call-to defibrillation time could not be sufficiently reduced (eg, b 10 minutes).…”
Section: Early Defibrillation Programs In Urban Areas Outside Emsmentioning
confidence: 92%